Adverse childhood experiences, mindfulness and happiness in Chinese college students during the COVID‐19 pandemic - Huang, Chien‐Chung (Child Fam Soc Work, 2021)
The rise of literature on adverse childhood experiences (ACEs) has indicated a strong relationship between ACEs and negative life outcomes, leading to important implications for services to the population. However, less is known about the effects of ACEs on happiness and the role of mindfulness in this relation. This study examined the relationships between ACEs and happiness and whether mindfulness mediated the effects of ACEs on happiness in a sample of Chinese college students. The data were collected from 1871 college students from 12 colleges across China in September 2020. The findings of this study show that ACEs had significant negative effects on students' happiness and that mindfulness helped to substantially reduce the negative effects of ACEs on happiness. Students who experienced emotional neglect and abuse in childhood were affected the most. By contrast, this group is not the primary focus of mindfulness‐based interventions in existing literature; thus, this study calls for specific mindfulness‐based interventions for this vulnerable population.